THE EFFECT OF WORK DISCIPLINE ON SERVICE PERFORMANCE AND ITS IMPLICATIONS ON COMMUNITY SATISFACTION AT THE CLASS I IMMIGRATION OFFICE IN JAKARTA UTARA - Tuswoyo; Pudji Hidajatun (Journal Indonesia Law and Policy Review, 2021)
The purpose of this study to determine the effect of work discipline on service performance and its implications on community satisfaction in the Immigration Office Class I North Jakarta. This research is a quantitative field research. Field research is a study to obtain data that actually occurs in the field. While quantitative means to emphasize the analysis of numerical data (numbers) obtained by statistical methods. The method used in this research is Survey Explanatory research method. The population in this study is the average customer per month who use the services of Immigration Office Class I North Jakarta as many as 1500 people, the researchers took a sample of 10% of the population. Thus 10% of the 1500 is 150. So the sample in this study amounted to 150 customers of the Immigration Office Class I North Jakarta. Based on the analysis, it is known that the value of t count is 8,942. This value is compared with the value of t table, with df = 148 obtained t value table 1.976. After compared it t value is bigger than t table value (8.942 > 1.976). This means there is a significant effect of mediation. Thus it can be concluded that Employee discipline affects the satisfaction of society through service performance. The strength of work discipline variable (X) which directly affects the variable of community satisfaction (Z) is 0.02% and through the relationship of service performance variable (Y) of 0.9%. Thus, the total work discipline variable (X) affects the variable of community satisfaction (Z) with the mediation of service performance (Y) of 0.92%. Based on these results it can be concluded that the amount of work discipline variables (X) and mediation of service performance variables (Y) together influence the variable of community satisfaction (Z) of 93.9%. The magnitude of influence proportionally caused by other variables outside the work discipline variables (X) and mediation variable service performance (Y) of 6.1%.